The effects of etomidate on testicular ischemia reperfusion injury in ipsilateral and contralateral testes of rats - (:unkn) unknown (VERDUCI PUBLISHER, 2022)
OBJECTIVE: Testicular torsion is a condition that manifests with acute pain and can lead to infertility despite urgent surgical intervention. The aim of this study is to investigate the protective and preventive effects of etomidate, an imidazole derivative, a non-barbiturate general anesthetic agent, without analgesic effect, on testicular ischemia-reperfusion injury. MATERIALS AND METHODS: Twenty-four adult male Wistar rats weighing 200-250 g were used in the study. Torsion was created in all rats by rotating left testes 720 degrees clockwise on the day of the experiment. 30 minutes before detorsion, 4 mg/kg etomidate and 10 mg/kg propofol were administered intraperitoneally to the etomidate and propofol groups, respectively. After an hour of ischemia, the left testis was reinstated, and the tissues were repaired according to their physiology. Following 24 hours of reperfusion, the animals were euthanized after ipsilateral and contralateral testes were removed. RESULTS: Etomidate applied before testicular detorsion significantly suppressed germ cell damage and Leydig cell loss in ipsilateral tissue. It did not cause any significant changes in the percentage of necrosis, histological score, and tubule rupture in ipsilateral tissue. Propofol administered before testicular detorsion significantly suppressed the percentage of necrosis only in the ipsilateral tissue. In addition, no signs of damage were observed in the contralateral testis. CONCLUSIONS: These findings show that etomidate administered before detortion creates a protective effect by preventing testicular ischemia-reperfusion injury.
Keywords: General anesthetic; Germ cell; Leydig cell; Testicular torsion and detorsion; Ischemia reperfusion injury; Ipsilateral and contralateral testes; PROPOFOL; TORSION; DURATIONS; APOPTOSIS